Treatment with intravenous immunoglobulin modulates coagulation- and complement-related pathways in COVID-19 patients - McGrosso, Dominic; Raygoza, Jessica; Kumar, Avnee J.; Lam, Michael T. Y.; Barnes, Laura A.; Karandashova, Sophia; Perryman, Alexia; Geriak, Matthew; Odish, Mazen F.; Coufal, Nicole G.; Lichtenstein, Brian; Sakoulas, George; et al. (Frontiers in Immunology, 2025)
IntroductionIntravenous immunoglobulin (IVIG) is a therapy that uses pooled immunoglobulins from thousands of different donors. While it is primarily used to treat immunodeficiency and autoimmune diseases due to its immunomodulatory properties, IVIG has also been used as an off-label therapy for respiratory infections, including COVID-19. Clinical data regarding the efficacy of IVIG for COVID-19 has been controversial, and although some smaller studies have shown beneficial effects, others including a large randomized trial found no significant clinical impact but noted detrimental secondary effects.MethodsWe describe the first proteomic analysis from the plasma of COVID-19 patients treated with IVIG, as well as clinical outcomes.ResultsPatients that received IVIG early upon hospitalization have faster clinical improvement. Proteomic analysis showed that serum from patients with COVID-19 has increased levels of proteins associated with inflammatory responses, activation of coagulation and complement pathways, and dysregulation of lipid metabolism. IVIG therapy significantly impacted pathways related to coagulation. Given known crosstalk between coagulation and complement pathways, we also analyzed complement-related proteins. Overall, treatment with IVIG appeared to modulate coagulation (KNG1, ACTB, FGA, F13B, and CPB2) and complement (C1RL, C8G and CFD) related proteins.DiscussionOur data is supported by similar findings observed in disease states other than COVID-19, where IVIG can impact coagulation and complement proteins. However, early administration seems to be critical determinants to optimize responsiveness to IVIG therapy in COVID-19.